Strategi Pengembangan Pariwisata Melalui Pendekatan City Branding Lebak Unique Di Kabupaten Lebak - Reza Fauzan (Journal of Citizenship, 2025)
The tourism sector has become a new industry that can provide rapid economic growth in terms of job opportunities, income, living standards, and activating other production sectors. Lebak Regency has the potential to be one of the priorities for enhancing economic growth in order to achieve community welfare. This study examines the tourism development strategy of lebak unique through the city branding approach in Lebak Regency. The concept used in this study is city branding from Insch (2011). The research method uses qualitative research methods. According to Insch, there are four d imensions of City Branding analysis, namely: identity, objective, communication, and coherence. While the research method used is a qualita tive method. The results of the study show that: a tourism development strategy of Lebak Unique through a city branding approach in Lebak Regency has been carried out based on 4 dimensions namely, 1) Identity, 2) Objective, 3) Communication, and 4) Coherence). The Lebak Regency Government emphasizes the tourism sector to support city branding. Then, it is also known that the strength of city branding in Lebak Regency lies in the dimensions of communication and commitment because there is a new dimension of communication and commitment. The communication carried out by the Lebak Regency Government is using persuasive communication including primary, secondary, and tertiary. Therefore, with this persuasive communication, there is a commitment from stakeholders to always jointly promote and develop tourism in Lebak Regency